Implementasi Decision Support System Penentuan Penerimaan Bantuan Untuk Siswa Kurang Mampu Menggunakan Metode Promethee - Satifa, Risa; Zakaria, Hadi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
MI Raudlatul Athfal is an Islamic Education School under the auspices of the Nurush Shodiqin Foundation located in Kp. Rawa Panjang, Bojonggede, Kab. Bogor. The number of students attending MI Raudlatul Athfal is approximately 520 students. The main problem faced is the difficulty of determining which students are entitled to receive assistance for underprivileged students who attend Mi Raudlatul Athfal, and the school also does not have a system that can determine students to receive assistance appropriately and accurately. Determination of students who are entitled to receive assistance is more often subjective, the determination is based on individual teacher assessments, so that the students selected do not match the criteria set by the school. To overcome this problem, the author conducted research using the Promethee Method or Preference Ranking Organization Method for Enrichment Evaluation to determine educational assistance from the school. This research aims to design a Decision Support System (DSS) to determine recipients of assistance for underprivileged students at MI Raudlatul Athfal. This system uses the Promethee method to calculate the preference value for each child based on several criteria that have been determined as a condition for determining aid recipients for underprivileged students at MI Raudlatul Athfal. In this research, the author used the JavaScript programming language and MySQL database as data storage.